Interacting metal and ligand based open shell systems: Challenges for experiment and theory - Kaim, Wolfgang; Paretzki, Alexa (Coordination chemistry reviews, 2017)
[Display omitted] •Analysis of oxidation and spin state situations is described for selected M-L-M and L-M-L systems.•The value of combining various experimental and computational methods is emphasized.•A complete array of complexes Ru-L-Ru with metal/ligand oxidation state ambivalence is presented.•Redox-active hemilabile ligands Q can form radical states with spin coupling potential to Co, Ni and Cu. Three-center bridged situations Ru-L-Ru and Q-M-Q (M=Ru, Co, Ni, Cu) containing redox-active transition metals and noninnocently behaving ligand redox systems Lk or Qn (o-iminoquinone/o-iminosemiquinone/o-amidophenolate series) can provide valuable insight into electronic and spin interactions of correlated coordination compounds. Experimental approaches using combined structural, electrochemical, spectroscopic (UV–vis-NIR) and magnetic resonance methods were employed with computational support to elucidate which of the potential alternatives are most appropriate to describe the individual electronic structures.